Development of nanoemulsion containing Sirih (Piper betle) essential oil as pesticide formulation - Yaakub, Haslina (2018)
The objectives of this research was to produce new formulation of nanoemulsion containing Piper betle essential oil, characterize the essential oil of the Piper betle, nanoemulsion and nanoemulsion containing P. betle essential oil and also to determine the effectiveness of P. betle as the natural nanopesticide. The dark yellow colour of P. betle essential oil was obtained by using hydro distillation process while nanoemulsion was fonnulated by using spontaneous emulsiﬁcation method. The point used to formulate nanoemulsion was obtained from pseudo phase diagram for the system (soybean oil + Tween 80 + glycerol + water) of previous research where 60% surfactant, 30% water and 10% soybean oil used. The size of blank nanoemulsion and nanoemulsion containing P. belle essential oil were 119.68 nm and 24.81 nm respectively. All the test conducted to test validity of essential oil and nanoemulsion show the positive result. However, the bioassay test conducted to test effectiveness of nanoemulsion containing P. betle essential oil was failed to get expected result due to unsuitable test conducted and higher concentration of essential oil than nanoemulsion containing P. betle essential oil concentration.